The Impact of Virtual Clinic Services on Healthcare Practitioners’ Attitudes: A Case Study at Maternity and Children Hospital Makkah al Mukarramah, Saudi Arabia - Misfer A. Asiri; Judy Jenkins; Jomin George; Aalia A. Hayat; Jalal H. Meny; Hassan H. Al-Qurashi; Emad N. Alsubhi; Saad A. Almalki (Journal of Pharmacy and Bioallied Sciences)
Aims and Objectives: This study examines healthcare practitioners’ attitudes toward virtual clinic (VC) services at the Maternity and Children Hospital (MCH) in Makkah, Saudi Arabia. Materials and Methods: Using a modified questionnaire based on the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model, data from 212 health practitioners was analyzed. Descriptive, regression and graphical analyses were performed using R software. Results: A P-value of less than 0.05 was considered significant. Results indicate significant associations between factors such as performance expectancy (0.022|), perceived value (0.004), social influence (0.002), facilitating conditions (0.002), hedonic motivation (0.029), and habit influence (0.035), and healthcare practitioners’ attitudes toward virtual clinic use. The only factor that did not significantly influence attitudes was effort expectancy (0.152). More than 61.61% of the respondents expressed a positive attitude toward using virtual services. Conclusion: The study highlights the increasing adoption of VC services post-COVID-19 and underscores the importance of addressing challenges such as digital infrastructure and expertise gaps.